Inspection of Bulk Crystals for Quality Control in Crystal Growth: Assessment of High-Energy X-Ray Transmission Topography and Back-Reflection Topography Pinpointed for Physical Vapor Transport-Grown Aluminum Nitride - Weingärtner, Roland; Epelbaum, Boris; Lesnik, Andreas; Lukin, Gleb; Müller, Stephan; Schiller, Leon; Meissner, Elke; Weißer, Matthias; Besendörfer, Sven (Crystals, 2025)
A comprehensive X-ray topography analysis of two selected aluminum nitride (AlN) bulk crystals is presented. We compare surface inspection X-ray topography in back-reflection geometry with high-energy transmission topography in the Lang and Laue configuration using the monochromatic Kα1 excitation wavelength of copper, silver, and tungsten, respectively. A detailed comparison of the results allows the assessment of both the high- and low-energy X-ray topography methods with respect to performance and structural information, giving essential feedback for crystal growth. This is demonstrated for two selected AlN freestanding faceted crystals up to 8 mm in thickness grown in all directions using the physical vapor transport (PVT) method. Structural defects of all facets of the crystals are determined using the X-ray topography in back-reflection geometry. The mean threading dislocation densities are 480 ± 30 cm−2 for both crystals of either the Al- or N-face. Clustering of dislocations could be observed. The m-facets show the presence of basal plane dislocations and their accumulation as clusters. The integral transmission topographs of the (Formula presented.) (m-plane) reflection family show that basal plane dislocations of the screw type in (Formula presented.) directions decorate threading dislocation clusters. Three-dimensional section transmission topography reveals that the basal plane dislocation clusters mainly originate at the seed boundary and propagate in the (Formula presented.) direction along the growth front. In newly laterally grown material, the Borrmann effect has been observed for the first time in PVT-grown bulk AlN, indicating very high structural perfection of the crystalline material in this region. This agrees with a low mean FWHM of 10.6 arcsec of the (Formula presented.) reflection determined through focused high-energy Laue transmission mappings. The latter method also opens the analysis of the (Formula presented.) -shift correlated to the residual stress distribution inside the bulk crystal, which is dominated by dislocation clusters. Contrary to Lang transmission topography, the de-focused high-energy Laue transmission penetrates the 8 mm-thick crystal enabling a defect analysis in the bulk.
CRIS-Team Scopus Importer:2025-06-06
Keywords: AlN bulk crystals; basal plane dislocations; crystal boules; dislocation clusters; dislocation density; Lang topography; Laue topography; threading dislocations; X-ray topography